Gadget Use Correlated with Emotional Development in Preschool Children - Annif Munjidah; Siti Noer Diana; Yasi Anggasari; Elly Dwi Masita (Journal of Ners and Midwifery, 2025)
Children who often use gadgets at home have a bad impact, children become unwilling to play outside the house and interact with others to behave aggressively. Nowadays, children's emotional development is a problem that is often conveyed by parents to teachers at school. This study aimed to examine the correlation between gadget use and the emotional development of preschool children at Tunas Jaya Kindergarten, Surabaya. This study used an observational analytic design with a cross-sectional approach. From the population of 59, 53 respondents were selected as the sample through a simple random sampling technique. The variables being studied were gadget use and emotional development in which data were collected using a gadget use questionnaire and ASQ: SE-2 questionnaire. Data processing was conducted by editing, scoring, coding, tabulating, processing, and cleaning. Moreover, the data were analyzed using the Spearman Rho Correlation Test in SPSS with a significance level of α = 0.05. The results revealed the high use of gadgets by the majority of the preschool children (96%), while 45.3% experienced emotional development categorized as "refer." The p-value = 0.000 indicated that there was a correlation between gadget use and emotional development in preschool children. This study concluded that there is a relationship between gadget use and the emotional development of preschool children. It is recommended that preschool children should not use gadgets more than 3 times a day and avoid using them daily. so as not to bring negative impacts on them.